Interleukin‐17‐ and interleukin‐22‐secreting myelin‐specific CD4+ T cells resistant to corticoids are related with active brain lesions in multiple sclerosis patients. Issue 2 (2nd December 2015) - Wing, Ana Cristina; Hygino, Joana; Ferreira, Thais B.; Kasahara, Taissa M.; Barros, Priscila O.; Sacramento, Priscila M.; Andrade, Regis M.; Camargo, Solange; Rueda, Fernanda; Alves‐Leon, Soniza V.; Vasconcelos, Claudia Cristina; Alvarenga, Regina; et al.
Summary: Multiple sclerosis (MS) is thought to be an autoimmune disorder. It is believed that immunological events in the early stages have great impact on the disease course. Therefore, we aimed to evaluate the cytokine profile of myelin basic protein (MBP)‐specific T cells from MS patients in the early phase of the disease and correlate it to clinical parameters, as well as to the effect of in vitro corticoid treatment. Peripheral T cells from MS patients were stimulated with MBP with our without hydrocortisone for 5 days. The cytokines level were determined by ELISA. The number of active brain lesions was determined by MRI scans, and the neurological disabilities were assessed by Expanded Disability Status Scale scores. Our results demonstrated that MS‐derived T cells responded to MBP by producing high levels of T helper type 1 (Th1) and Th17 cytokines. Although the production of interleukin‐6 (IL‐6), granulocyte–macrophage colony‐stimulating factor, IL‐17 and IL‐22 was less sensitive to hydrocortisone inhibition, only IL‐17 and IL‐22 levels correlated with active brain lesions. The ability of hydrocortisone to inhibit IL‐17 and IL‐22 production by MBP‐specific CD4 + T cells was inversely related to the number of active brain lesions. Finally, the production of both cytokines was significantly higher in cell cultures from Afrodescendant patients and it was less sensitive to hydrocortisone inhibition. In summary, our data suggest that IL‐17‐ and IL‐22‐secreting CD4 + T cells resistant to corticoids are associated with radiological activity of the MS in early stages of the disease, mainly among Afrodescendant patients who, normally, have worse prognosis.